Odpowiedzi

2010-02-09T21:30:46+01:00
-x/2=3x-3+2x/4
-x = 6x - 6 + 2x/2
-2x = 12x - 12 + 2x
12 = 16x
x = 16/12
x = 1,3

3- 3x/2= 5/8-4x-3/6
24*3 - 12*3x = 3*5 - 24*4x - 4*3
72 - 36x = 15 - 96x - 12
60x = -69
x = -69/60
x = 1,15

3-2x/5+8=5x+2/2-x
30-4x + 80 = 50x + 10 - 10x
100 = 44x
x = 44/100
x = 0,44

2x-11/4+19-2x/2=2x
8x-11+19*4-4x=8x
65 = 4x
x = 65/4
x=16,25
2010-02-09T21:33:12+01:00
-x/2=3x-3+2x/4 |*4
-2x = 12x - 12 + 2x
-2x -12x - 2x = -12
-16x = -12 |:(-12)
x = 12/16
x = ¾

3- 3x/2= 5/8-4x-3/6 |*24
72 - 36x = 15 - 96x - 12
-36x + 96x = 15 - 12 - 72
60x = -69 |:60
x = -1,15


3-2x/5+8=5x+2/2-x |*10
6 - 4x + 80 = 25x + 10 - 10x
-4x - 25x + 10x = 10 - 6 - 80
-19x = -76 |:(-19)
x = 4
(w tym przykłądzie ledwo się połapałam z ulamkami, ale teraz wiem jak to miało być :))

2x-11/4+19-2x/2=2x |*4
8x - 11 + 76 - 4x = 8x
8x - 4x - 8x = 11 - 76
-4x = -65 |:(-4)
x = 16 ¼